Partially Mobile Adsorption of Single Gases on Graphitized Carbon Black Surfaces - J.K. Garbacz; H. Kowalczyk-Dembińska; A. Dabrowski (Adsorption Science & Technology)
An expression for the isosteric heat of partially mobile monolayer adsorption of a single gas on a heterogeneous adsorbent surface has been derived. Optimizations of the model parameters have been performed for selected experimental systems containing graphitized carbon black as an adsorbent.